2018
DOI: 10.1002/nafm.10036
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile and Adult Striped Bass Mortality and Distribution in an Unrecovered Coastal Population

Abstract: Striped Bass Morone saxatilis fisheries have been important in the eastern United States since the 1700s, but many populations have declined from historic levels. Enhancement programs, harvest reduction, water quality improvements, and habitat restoration have led to successful recoveries for specific stocks. However, these efforts have not been successful for the Striped Bass population in the Neuse River of North Carolina. Possible mechanisms inhibiting recovery of this population include overharvest, high d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Vital rate parameter estimation.-Stage-and source-specific mortality rates were available for the Neuse River Striped Bass population (Table 1; NCDMF and NCWRC 2013;Bradley et al 2018). Mortality of phase II hatcheryreared juveniles, total mortality of adults, and natural mortality of adults were reported by Bradley et al (2018). We calculated fishing mortality by assuming that total mortality was a fully additive form of natural and fishing mortality, which occurred continuously throughout the year:…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Vital rate parameter estimation.-Stage-and source-specific mortality rates were available for the Neuse River Striped Bass population (Table 1; NCDMF and NCWRC 2013;Bradley et al 2018). Mortality of phase II hatcheryreared juveniles, total mortality of adults, and natural mortality of adults were reported by Bradley et al (2018). We calculated fishing mortality by assuming that total mortality was a fully additive form of natural and fishing mortality, which occurred continuously throughout the year:…”
Section: Methodsmentioning
confidence: 99%
“…Ongoing research programs have estimated stage-and source-specific mortality rates in an effort to identify mechanisms associated with the lack of recovery of the Neuse River Striped Bass population. For example, Bradley et al (2018) acoustically tracked 100 hatchery-reared phase II juvenile Striped Bass and 111 resident adults in the Neuse River. They concluded that 66% (95% credible interval [CI] = 47-82%) of juveniles died within the first year after stocking and that adult mortality was lower (annual discrete total mortality = 0.54, 95% CI = 0.43-0.66; annual discrete natural mortality = 0.20, 95% CI = 0.09-0.39).…”
mentioning
confidence: 99%
See 2 more Smart Citations